Design and measurement of a compact MIMO antenna using C-shaped metamaterial for 5G/6G wireless communication circuit - Shobhit K. Patel; Abdullah Baz (Alexandria Engineering Journal, 2025)
The need for high-speed communication in today’s world requires an antenna that has not only has high gain but also ultra-wideband response. Two such MIMO antennas are designed in this research which operating in the GHz and THz regime. The fractal MIMO antenna is initially designed with four square patches which providing a bandwidth of 5 THz and a gain of 15.1 dBi. The antenna is observed over a spectrum range of 5–50 THz. The results of the square patch fractal MIMO antenna are enhanced by cutting slits in it and adding a small line above the patch which creates a metamaterial effect. The metamaterial fractal MIMO antenna provides a bandwidth of 44.8 THz and a gain of 25.6 dbi. The metamaterial loading has improved both the antenna’s bandwidth and gain. The metamaterial parameters are also observed in this research, showing a double negative behavior. The physical parameters of the design are optimized to get the best results for the metamaterial antenna. The MIMO performance parameters, such asvvv ECC (near zero from 15 THz to 29 THz, and from 30 THz to 50 THz} DG (10 dB), MEG (near zero from 10 THz to 15 THz) TARC (negative), and CCL (near 0.1), are also investigated in this research. The MIMO antenna is designed and fabricated for GHz regime and the measured results show good agreement with simulated results. The GHz antenna results are applicable to 5 G communication circuit. The finite element method is used for the performance analysis of the proposed design. The proposed metamaterial fractal MIMO antenna, with its ultra-wideband response and high gain, is suitable for wearable applications and 6 G wireless communication devices.